Assessment of the appropriateness of stress ulcer prophylaxis use and its determinants among admitted surgical patients at Debre Berhan University Hakim Gizaw Hospital, Ethiopia. A hospital-based cross-sectional study - Tsige, Abate Wondesen; Beyene, Dessale Abate; Wondmkun, Yehualashet Teshome; Endalifer, Bedilu Linger; Habteweld, Habtemariam Alekaw; Gebretadik, Fissha Assegidew; Gebeyehu, Aregahegn Adafir; Azene, Belayneh Abebaw; Alamneh, Misganaw Abebaw; Tesfaye, Daniel Zebene; Fered, Misganaw Aynalem; Girma, Mandefro Teje; et al. (Frontiers in Medicine, 2024)
Introduction: Pharmacological stress ulcer prophylaxis (SUP) has been recommended for many years to reduce the risk of clinically significant upper gastrointestinal (GI) bleeding caused by stress ulcers. Stress-related ulcer bleeding in surgical patients significantly increases morbidity and mortality. Therefore, preventing stress-induced hemorrhage is the most appropriate measure for patients who are at increased risk. However, the inappropriate use of SUP has increased in recent years, and its use in Ethiopian surgical patients has not been well studied.